Assessment of the preventive activity of Pinus brutia Ten. (Pinaceae) against in vivo acute lung injury model - Suntar, Ipek; Demirel, Muerside Ayse; Taban, Kevser; Ceribasi, Ali Osman; Gok, Hasya Nazli; Metkin, Gulsum (Elsevier, 2023)
Acute lung injury is a crucial inflammation-induced lung complication. Acute respiratory distress syndrome, which has a more severe course and is characterized by diffuse infiltration, develops with the progression of acute lung injury. The incidence of acute lung injury and acute respiratory distress syndrome is high and are both associated with increased mortality and morbidity rates worldwide. The leaves (needles) of Pinus brutia Ten. (Pinaceae) have been traditionally used against bronchitis and asthma. In addition, there are many Turkish folk medicine records regarding the use of its cones in respiratory system diseases such as cough, hoarseness, lung diseases, bronchitis, asthma, tuberculosis, and pneumonia. The present study aims to comparatively investigate the in vivo biological activity of the needles and cones of P. brutia against Acute Lung Injury (ALI) and to evaluate its potential use. The extracts of P. brutia needles and cones were investigated in ALI model in rats. Male Sprague Dawley rats were divided into sham control, lipopolysaccharide (LPS), reference, and six treatment groups. ALI model was induced by intraperitoneal (i.p.) LPS (5 mg/kg) injection. One hour before LPS administration, needle and cone extracts of the P. brutia at doses of 100, 200, and 400 mg/kg were given to the treatment groups. Carboxymethyl cellulose aqueous solution (0.5%) was given to the sham control group and LPS group. Dexa-methasone (1.5 mg/kg) was administered to the reference group. In the 4th hour after LPS administration, in-flammatory cells were counted in bronchoalveolar lavage fluid (BALF), and the levels of interleukin (IL)-6 and -8, and tumor necrosis factor-alpha (TNF-alpha) were measured by enzyme-linked immunosorbent assay (ELISA). Oxidative stress index (OSI) values and peroxiredoxin (PRDX)-1 gene expression in lung tissues were calculated by quantitative real time polymer chain reaction (RT-PCR). Histopathological examination was performed by Hematoxylin Eosin (HE) and Masson Trichrome (MT) staining methods. In addition, the amounts of the phenolic compounds were determined by High Performance Liquid Chromatography (HPLC). Catechin hydrate and vanillic acid were determined to be higher; taxifolin was lesser in the cone extract than the needle extract. The best improvement in the macroscopic appearance of the lungs was observed in the cone extract (200 mg/kg) group compared to the other treatment groups. While the percentage of inflammatory cells in BALF was increased in the LPS group, these cells were in the lowest rate in the cone extract (200 mg/kg) group. Both needle and cone extracts decreased the levels of inflammatory cytokines. The OSI values in the treatment groups decreased compared to the LPS group. PRDX-1 levels were the highest in the LPS group, but this level dropped in the treatment groups. The inflammation of the lung tissue in the LPS group was higher than in the other groups. The recovery of inflammation was similar to both needle and cone extracts of P. brutia. These data provide evidence that 200 mg/kg of the cone extract is a potential candidate for the prevention of ALI and warrants further preclinical evaluation.
Keywords: Acute lung injury; Anti-inflammatory; Antioxidant; Pinaceae; Pinus brutia